(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2025)
This article discusses the modern approaches to early diagnosis and treatment of uterine body cancer, focusing on innovative methods such as advanced screening techniques, laboratory diagnostics, and effective treatment strategies. The study emphasizes the importance of timely detection and highlights the role of multidisciplinary approaches and advanced technologies in improving treatment outcomes and patient survival rates.